ICT-Mediated Adaptive Capacity of Environmental Third Sector in Australia - Dhakal, Subas P. (Journal of Community Informatics, 2014)
Australia has relied extensively on thousands of environmental third sector organisations (ETSOs) to care and plan for environmental protection. Although the potential of information and communication technologies (ICTs) to enable these organisations has been increasingly recognised ETSOs in general have slipped under the radar of ICT-oriented practices. The aim here is to respond to this gap and examine the differences in adaptive capacity between ICT adopter and non-adopter ETSOs in Perth, Western Australia. Based on the findings, which indicate that the majority of organisations are either overlooking or under-exploiting the potential of ICTs, it is recommended that existing environmental strategies that rely on ETSOs need to institutionalise ICT-specific support for these organisations.